The effect of corporate income tax rates, leverage, and inventory intensity on tax avoidance - Ni Kadek Santika Dewi; Subagio Subagio (Educoretax, 2026)
This research is motivated by the low tax ratio in Indonesia, which is partly caused by tax avoidance practices carried out by corporations. Therefore, it is important to understand the key factors influencing corporate tax avoidance. This study aims to analyze the effect of the corporate income tax rate, leverage, and inventory intensity on tax avoidance. The research sample consists of property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2024 period. A quantitative approach is employed, using secondary data in the form of annual financial statements. The sample is selected using purposive sampling and analyzed with a panel data regression using the random effect model. The results show that, partially, the corporate income tax rates and leverage have no significant effect on tax avoidance. Meanwhile, inventory intensity has a negative and significant effect on tax avoidance, which may be due to the companies' transparent disclosure of inventory in their financial statements. However, simultaneously, the three variables have a significant effect on tax avoidance. These findings indicate that operational characteristics, particularly inventory intensity, play an important role in determining tax avoidance strategies. Therefore, regulators should consider internal corporate factors when designing more effective tax policies in the property and real estate sector. Property and real estate companies are also encouraged to disclose their inventories transparently.